Evaluating hand hygiene knowledge, attitudes, and practices among healthcare workers in post-pandemic H1N1 influenza control: a cross-sectional study from China - Hong, Qin; Xu, Yuling (Frontiers in Public Health, 2024)
Background: This study evaluates the knowledge, attitudes, and practices (KAP) of hand hygiene among healthcare workers, crucial for preventing healthcare-associated infections (HAIs) in medical facilities. Methodology: This cross-sectional study assessed hand hygiene KAP among healthcare workers across various settings in Hubei, China utilizing a stratified random sampling approach from, December 25, 2023-to-April 25, 2024. A bilingual electronic survey, adapted from validated tools, was disseminated via email and social media to ensure a broad reach. Participants included diverse healthcare professionals who met specific inclusion criteria. Responses were analyzed using R software, employing descriptive and inferential statistics to identify key predictors of hand hygiene behavior and to confirm the reliability of the survey instrument. Results: The survey of 2,265 healthcare workers revealed that 77% demonstrated comprehensive knowledge of hand hygiene, 80% exhibited positive attitudes, and 94% practiced effective hand hygiene. Notable findings include a significant understanding of hand hygiene’s role in preventing respiratory illnesses (58%) and HAIs (41% agreed, 39% unsure). High compliance in practices like washing hands for at least 20 seconds was evident (84%), though gaps in confidence about hand hygiene techniques were noted (33% confident, 56% unsure). Binary logistic regression analysis indicated that younger healthcare workers (21-30 years) were more likely to exhibit both knowledge (OR=7.4, 95% CI=1.44-136, p=0.059) and positive attitudes (OR=4.48, 95% CI=1.73-11.8, p<0.001) compared to other age groups. Significant associations were found between higher income levels and positive attitudes towards hand hygiene (OR for ≥80,000=3.19, 95% CI=2.05-5.02, p<0.001), and between knowledge and practices, suggesting that well-informed individuals are more likely to adhere to recommended practices. Conclusion: The findings reveal robust hand hygiene knowledge but uncover critical confidence gaps among healthcare workers, urging immediate, targeted educational interventions to fortify adherence and prevent infection outbreaks.